APPLICATION OF THE LEX SPECIALIS DEROGAT LEGI GENERALIS PRINCIPLE IN HOUSEHOLD VIOLENT CRIMINAL CASES WITH UNDER HAND MARRIAGE STATU: STUDY OF DECISION NUMBER 101/PID.B/2018/PN KPH - Harsandini, Diska; Haeranah; Azisa, Nur (Universitas Islam Negeri Alauddin Makassar, 2023)
The case against Decision Number 101/Pid.B/2018/Pn Kph with the application of Article 351 paragraph (1) of the Criminal Code in criminal cases of domestic violence, as well as the application Law No. 23 of 2004 concerning Domestic Violence for victims of domestic violence with underhanded marriage ties that are not in line with legal objectives in terms of certainty, justice and benefit. This research is a normative legal research using a statutory approach. The results of the research show that the application of Article 351 paragraph (1) of the Criminal Code does not fulfill the legal objectives in terms of certainty, justice, and legal benefits. This is due to the fact that the panel of judges, through their considerations, does not see that underhand marriage is a legal marriage, whereas in the KHI and the Marriage Law it is considered that marriages carried out in accordance with religious verses are legal marriages, so that the application Law No. 23 of 2004 concerning Domestic Violence can be applied as a legal basis. Implementation the Law No. 23 of 2004 concerning Domestic Violence can be applied to victims of domestic violence with underhanded marriage ties, based on the KHI and the Marriage Law, this is also strengthened by The Lex Specialis Derogat Legi Generalis so that victims of domestic violence with underhand marriage ties are no longer only protected by general regulations, namely the Criminal Code, but special regulations, namely Law No. 23 of 2004 concerning Domestic Violence Law (PKDRT).